Sandwich-type ferrocene-functionalized magnetic nanoparticles: synthesis, characterization, and the adsorption of Cr(VI) - Danyang, Liu; Yimin, Dai; Jiaqi, Zou; Shengyun, Wang; Qi, Lu; Ling, Chen (Journal of materials science. Materials in electronics, 2019)
In this paper, novel ferrocene functionalized sandwich-type core–shell structure magnetic nanocomposites (Fe 3 O 4 @SiO 2 –FC/COOH) are synthesized using the Fe 3 O 4 as the core and the ferrocene and 5-Aminoisophthalic acid as the functional dendrimers. Taking advantage of high redox activity benefit of ferrocene, Fe 3 O 4 @SiO 2 –FC/COOH is fabricated to adsorb Cr(VI) and reduce it to nontoxic Cr(III) in aqueous solution. The structure and morphology of prepared magnetic adsorbent are characterized by FTIR, XRD, SEM, XPS, TEM, EDS, and TGA. Moreover, the effects of different factors (such as solution pH, adsorption time, adsorption temperature, adsorbent dosage etc.) on adsorption are evaluated. XPS analysis indicates that Cr(VI) is successfully reduced to nontoxic Cr(III) after adsorption by Fe 3 O 4 @SiO 2 –FC/COOH. The Fe 3 O 4 @SiO 2 –FC/COOH exhibits excellent removal efficiency with a maximum Cr(VI) adsorption of 228.395 mg g −1 at pH 2.0. In addition, the adsorption experimental results fit well with the Freundlich isotherm model and the pseudo-second-order kinetic model. Desorption experiment results demonstrate that the regenerated adsorption capacity can exceed more than 95% after five times adsorption–desorption cycles. Therefore, this work provides a promising approach for Cr(VI) removal from water solution.